2015
DOI: 10.1186/s40337-015-0083-x
|View full text |Cite
|
Sign up to set email alerts
|

Emotion dysregulation, self-image and eating disorder symptoms in University Women

Abstract: BackgroundWe studied associations between emotion dysregulation, self-image and eating disorder (ED) symptoms in university women, and contrasted two indirect effect models to examine possible intervening mechanisms to produce ED symptoms.Methods252 female Swedish university students completed the Difficulties in Emotion Regulation Scale (DERS), the Structural Analysis of Social Behavior (SASB) self-image measure, and the Eating Disorder Examination Questionnaire (EDE-Q). Correlations between scales were follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 60 publications
2
30
1
2
Order By: Relevance
“…For example, in a review of emotion regulation in AN and BN, Lavender and colleagues (Lavender et al, 2015) found many commonalities but a few specific emotion deficits in AN vs.BN (e.g., decreased emotion recognition/acceptance and heightened reward sensitivity, respectively), and research into OSFED presentations more similar to AN vs. BN may be guided by such findings. SASB self-image may be useful here also, as it has been shown to mediate the effect of emotion dysregulation on ED symptoms (Monell, H€ ogdahl, Fors en Mantilla, & Birgegård et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a review of emotion regulation in AN and BN, Lavender and colleagues (Lavender et al, 2015) found many commonalities but a few specific emotion deficits in AN vs.BN (e.g., decreased emotion recognition/acceptance and heightened reward sensitivity, respectively), and research into OSFED presentations more similar to AN vs. BN may be guided by such findings. SASB self-image may be useful here also, as it has been shown to mediate the effect of emotion dysregulation on ED symptoms (Monell, H€ ogdahl, Fors en Mantilla, & Birgegård et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment is described in detail elsewhere (Monell et al, 2015). Participants were rewarded with either a gift certificate or course credit depending on department affiliation.…”
Section: Participantsmentioning
confidence: 99%
“…Forsén Mantilla, & Birgegård, 2015;Svaldi, Griepenstroh, Tuschen-Caffier, & Ehring, 2012), symptom maintenance in anorexia nervosa (AN; Racine & Wildes, 2015), and outcome in bulimia nervosa (BN; MacDonald, Trottier, & Olmsted, 2017;Peterson et al, 2017). Generally, patients with EDs report more emotion dysregulation than controls (Brockmeyer et al, 2014;Mallorqui-Bague et al, 2018).…”
mentioning
confidence: 99%
“…Additionally, the mean effect size of the relationship between lack of emotional clarity and NSSI was also larger in adolescents than in adults. Apart from possessing more NSSI specific risk factors, adolescents also attach more importance to the clarity of emotions, because it is important for their development of self-identity [48,49]. When they cannot figure out what they are feeling or sense that their feelings are invalid or unimportant, adolescents may be more likely than adults to get frustrated and engage in NSSI.…”
Section: Research Min-pei Lin Jianing Youmentioning
confidence: 99%